2012
DOI: 10.9753/icce.v33.management.5
|View full text |Cite
|
Sign up to set email alerts
|

Future Extreme Waves at the German Baltic Sea Coast Derived From Regional Climate Model Runs

Abstract: Information about possible changes of extreme wave heights are essential for the future safe design of coastal and flood protection structures likes dykes, flood protection dunes, revetments etc. In this study, scenarios of regional climate change up to 2100 are used for the evaluation of changes of wave conditions. Analyses on calculated significant wave heights derived from extreme value statistics are showing a different signal of change for the selected locations along the German Baltic Sea Coast. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…the longshore sediment transport at sandy coasts (see e.g. Dreier et al, 2012). The results are not discussed in detail here, but a general trend of the changes of the 30 years annual averages of mean wave direction towards more westerly directions with maximum changes up to 7° at locations which are exposed to westerly winds are found (see Figure 9).…”
Section: Changes Of the Average Wave Conditionsmentioning
confidence: 90%
“…the longshore sediment transport at sandy coasts (see e.g. Dreier et al, 2012). The results are not discussed in detail here, but a general trend of the changes of the 30 years annual averages of mean wave direction towards more westerly directions with maximum changes up to 7° at locations which are exposed to westerly winds are found (see Figure 9).…”
Section: Changes Of the Average Wave Conditionsmentioning
confidence: 90%
“…These methods must take into account the specific characteristics of the data and the questions to be answered, namely amount and quality of the data, complexity of analysis, and demand on reliability of the result. Several publications show the variety of different methods which were used or specifically developed for the analysis [10] [11].…”
Section: Statistical Methods In Climate Change Analysismentioning
confidence: 99%
“…The wave dataset that has been analyzed was calculated by using a newly developed hybrid approach that consists of both empirical and numerical methods for the calculation of the wave conditions based on future projections of wind conditions from a regional climate model (COSMO-CLM [21] [22]) considering different future IPCC greenhouse gas emission scenarios (SRES [23]). The associated methods and results have been published in [10] [24].…”
Section: Example "Extreme Value Analysis"mentioning
confidence: 99%
“…The BACC group states an increase of the 90% percentile of the wave height of up to 0.5m for the Baltic Sea. Schlamkow et al (2012) showed (Fig.. 9)) that no clear tendency towards a general increase or decrease of extreme wave heights can be concluded from their analyses and that the results are spreading widely depending on different scenario runs and the projection periods. The results for increase / decrease of extreme wave heights spread between ± 15% for different scenario runs, which means that an increase of extreme wave conditions can not be excluded for the future.…”
Section: Extreme Eventsmentioning
confidence: 98%